Pass It On - Hadas, Rachel (Book collections on Project MUSE., 2014)
The poems in Rachel Hadas's new book are united by a common preoccupation with passage--passage variously construed. In Section I, the four seasons are glimpsed in turn through the lenses of several types of personal associations, especially parenthood. As spring gives way to fall and winter, separation looms; diverse kinds of temporary and permanent renewal come with spring, and the fifth poem in this section steps outside this cycle. In Section II, the phrase ""pass it on"" recalls the game ""telephone, "" in which a word is whispered by one speaker to another. Here the poems focus on trad